Intrapulse modulation recognition of signals based on statistical test of energy focusing efficiency - Guo-bing HU; Li-zhong XU; Shu-fang XU; Shan-shan WU; Yan GAO (Tongxin xuebao)
A blind intrapulse modulation recognition based on energy focusing efficiency test was proposed, which can be used to estimate the modulation type under low signal to noise ratio (SNR) conditions. The observed signals were pre-processed by short time filter defined in frequency domain in order to improve the processing SNR. Then, energy focus-ing efficiency feature was defined to identify modulation type of the signals depending on analysis of the condition for the single sinusoid generating among the six types of commonly used intrapulse modulation signals. The statistical test for the energy focusing efficiency was derived. Computer simulation results show that the proposed algorithm can be ef-fective to classify the commonly used intrapluse modulation signals under low SNR conditions.